The Influence of Instagram, Brand Image, and Price on Online Purchase Decisions - Bahri, Khoirun Nisa; Komaladewi, Rita (Asia Pacific Journal of Management and Education (APJME), 2023)
This paper aimed to examine the impact of social media Instagram, brand image, and price on online purchasing decisions on SME customers. The sample size in this study was 100 respondents from Atthahirah Clothing's customers. Structural Equational Modeling (SEM) with SmartPLS 3.0 program was used as the analysis technique. The results show that the use of Instagram has no significant effect on online purchasing decision, also consumers do not consider brand image when they make online purchasing decisions. Meanwhile, price positively affects online purchasing decisions. In conclusion, the biggest motivation for Atthahirah consumers in making online purchasing decisions is price. Therefore, pricing is important in determining online purchasing decisions for hijab fashion SMEs consumers.